1989
DOI: 10.1002/bbpc.19890930911
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Extraction of Citric Acid from an Aqueous Fermentation Broth

Abstract: The common precipitation process for the isolation of citric acid produces 2,5 tons of waste per ton citric acid. This paper presents a way to separate citric acid from a fermentation broth by avoiding the waste production of CaSO4. A combination of an extraction/reextraction process using a tertiary‐amine‐containing solvent was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 4 publications
0
31
0
Order By: Relevance
“…In a similar way, the Langmuir equilibrium model of Bauer et al 25 has been applied to relevant extraction systems along with considering an overall acid-extractant complexation with an associated number (z) relative to the maximum loading of the extractant,…”
Section: ( )mentioning
confidence: 99%
“…In a similar way, the Langmuir equilibrium model of Bauer et al 25 has been applied to relevant extraction systems along with considering an overall acid-extractant complexation with an associated number (z) relative to the maximum loading of the extractant,…”
Section: ( )mentioning
confidence: 99%
“…The recovery of citric acid from fermentation broth is one of important steps in a commercial process of citric acid production, especially from dilute solutions. Now, the only commercially viable technique on large-scale processes is precipitation technique using calcium salt followed by filtration and subsequently treated with sulphuric acid, but the common calcium salt precipitation process for isolation of citric acid produces 2.5 tons of waste per ton of citric acid [1][2][3][4]. Other recovery methods for this purpose, such as, solvent extraction, ionic exchange, absorption, electrodialysis, membrane separation, etc., encounter various difficulties [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In the final step, the acid is crystalized and dried. The main problem, associated with this process, is the requirement of resins to purify liquid phases and the huge amount of calcium sulfate generated [2]. Thus, alternative processes for citric acid recovery and purification from fermented musts have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Bauer et al [2] believe that the complexation reaction occurs with the citrate ions and trialkylamine in MIBK by an ionic association mechanism. Bízek et al [17], in their work with trialkylamine in MIBK, observed that both of the previously cited cases could occur simultaneously.…”
Section: Introductionmentioning
confidence: 99%